Maqâshid Al-Syarî`ah Paradigm for The Protection of Children Victims of Narcotics Abuse - Syahril Jamil; Muhammad Abdillah; Muhammad Torik (Jurnal Madania)
Narcotics often make children victims, it also affects the protection of children's rights. This study  is intended to see how maqâshid al-syarî`ah views the protection of child victims of narcotics. The method    used in this study is descriptive qualitative approach to explore how paradigms, factors and implications for the protection of child victims of narcotics. The data in this study was obtained through a search of a search engine google.com with the keyword " maqâshid al-syarî`ah paradigm towards legal protection of child victims of narcotics", then the data is reduced to be able to present the expected results in this study. The analysis of this study shows that legal protection for children victims of narcotics has not been fulfilled, so it is not uncommon for children to be used as agents for the sustainability of narcotics trafficking in Indonesia. This study is based on an argument that the protection of children entangled in drug cases is still not optimally provided both from prevention, legal process, and punishment of child victims of narcotics. As a results, a maqâshid al-syarî`ah approach is required, with the goal of achieving  advantage in offering legal protection regulations for children who are victims of narcotics in Indonesia.